THE IMPLEMENTATION OF DIAGNOSTIC APPROACH STRATEGY TO IMPROVE THE STUDENTS’ LISTENING SKILL - Koryati -; Nian Masna Evawati; Zulkifli - (Politeknik Negeri Sriwijaya, 2017)
The purpose of this study is to know the implementation of Diagnostic Approach strategy to improve the students’ listening skill. This study is part of a car action research and carried out by using descriptive research method in order to describe the implementation of the Diagnostic Aproach strategy. This study revealed interesting results. Not only the students can improve their listening score as shown by their higher post test score but they are also motivated to use various strategies to get the information needed in their listening activities.